Instrumental Dominance In Bands: a Study of Player Subjectivity - Manalu, Kartini R.M.; Simanjuntak, Hendrik L; Waruwu, Happy Majesty; Sagala, Yeremia Yosephina Van; Siahaan, Thessa Angelica (LPPM Universitas PGRI Sumatera Barat, 2025)
This research opens up a space for discourse on the existence of various perspectives of musicians and the community regarding the dominance of instruments. They believe that there is one instrument that has a higher 'value' than other instruments. In this case, ‘value’ can be interpreted as dominance, tendency, ‘primacy’, ‘existence’ and ‘position’ within a band or musical ensemble. The urgency of this research is to see to what extent this dominance is interpreted in a musical performance by musicians, the general public, and how this is connected to the concept of 'equality' from an instrumentation perspective. Something that becomes ‘blurry’ when an instrument is debated without a ‘balanced’ indicator or is diminuted from the character of the instrument.